Principal's Strategy for Increasing Accreditation in Junior High Schools - Maya Shaumi Idami; Cut Zahri Harun; Khairuddin Khairuddin (AL-ISHLAH: Jurnal Pendidikan, 2022)
Principals, as policymakers in schools, must function optimally. As a leader in educational institutions, the principal must be able to improve school accreditation in an effort to improve the quality of education. The purpose of this study was to obtain data and information regarding (1) the principal's strategy in increasing accreditation which was reviewed on the quality of graduates; (2) the principal's strategy in increasing accreditation through the learning process; (3) The principal's strategy in improving the accreditation status of teacher quality. The research approach is a descriptive method. The data collection techniques used were observation and interview. The research subjects were school principals and teachers, which consisted of six samples. The data analysis used was reduction techniques, data presentation, data interpretation and data verification. The results showed that the Principal of a state junior high school in Want Jaya in improving the accreditation status, improves the quality of three main components including (1) the quality of graduates is improved by focusing on increasing religious activities in schools, creating a bullying-free environment, improving skills, collaboration, critical thinking, and improve learning achievement; (2) the learning process is actively improved, holding remedial/enrichment programs, and moving the school literacy movement program (GLS); and (3) teacher quality improvement is carried out by increasing the ability to develop learning plans and continuous professional development. In addition, in realizing increased accreditation, the principal places himself as an educator, manager, administrator, supervisor, leader, and motivator. Each role is carried out as well as possible so that the role carried out by the principal can be achieved in accordance with the provisions.